Mastering business for strategic communicators : insights and advice from the C-suite of leading brands - Ragas, Matthew W., 1977-; Culp, Ron, 1947- (Emerald Publishing Limited, 2017)
The most successful communication professionals are no longer just communication experts - they are masters of business. To serve as trusted advisors to the C-suite and to collaborate across the enterprise means it is necessary to have a strong grounding in business acumen. Mastering Business provides strategic communications and public relations students and professionals with expert insights and advice into the various major business functions and departments. From an assemblage of top strategic communication leaders comes this collection of more than 20 essays from current and former Chief Communications Officers (CCOs). The authors show the business areas that communicators help convene, integrate, and translate across their enterprises and to external stakeholders. Each chapter features a Career Spotlight by the CCO and a C-suite View response from a business leader, including CEOs, presidents, and CFOs from household names like GE, GM, Southwest Airlines, Starbucks, Walgreens Boots Alliance, and SAP. This collection provides readers with a rare view of the leadership roles played by top strategic communicators inside some of today's most well-known brands and organizations.